The Effect of ESG Disclosure and Ownership Structure on Firm Value: The Moderating Effect of Profitability - Abdillah Arif Nasution; Annisa Rizki Pratiwi; Keulana Erwin (LifeSciFi, 2026)
This research is important to understand the factors that influence firm value in the manufacturing sector. This study aims to analyze the effect of ESG disclosure and ownership structure, which includes managerial ownership, institutional ownership, and foreign ownership, on firm value, with profitability as a moderating variable in manufacturing companies in the chemical and pharmaceutical subsectors listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative panel data regression approach with 10 chemical and pharmaceutical manufacturing firms listed on the IDX (2020–2024), analyzed using EViews 13. The results show that ESG disclosure has a negative and significant effect on firm value in manufacturing companies in the chemical and pharmaceutical subsectors listed on the IDX. Meanwhile, managerial ownership has a positive but insignificant effect on firm value. Institutional ownership shows a negative and insignificant effect on firm value, while foreign ownership has a positive but also insignificant effect on firm value. In addition, profitability is found to be unable to moderate the relationship between ESG disclosure, managerial ownership, institutional ownership, and foreign ownership on firm value in manufacturing companies in the chemical and pharmaceutical subsectors listed on the IDX.